Suklaakakku mukissa - Kemianluokka Gadolin (2020)
In this work we will make a delicious chocolate cake in a mug and inspect cooking from a chemist’s perspective. What chemical reactions happen in the batter when the cake is cooked? Or what are the roles of the ingredients in the cake? This work is an inspiring introduction to chemistry and is suitable for students of all ages.
Keywords: arkikemia; Kemianluokka Gadolin; Kemiklassen Gadolin; ChemistryLab Gadolin; innostaminen; molekyyligastronomia; molekylgastronomi; vardagskemi; inspiration; molecular gastronomy; excitement; everyday chemistry; LUMA-keskus Suomi; LUMA center Finland